"KAGONMA" NH3 mapping observations of molecular clouds with Nobeyama 45m telescope. Issue Volume 14:Issue S345(2019) (August 2018) - Murase, T.; Handa, T.; Maebata, M.; Yang, Z.; Hirata, Y.; Ishizaki, K.; Sunada, K.; Nakano, M.; Omodaka, T.; Shihara, S.; Wada, K.; Umemoto, T.; et al.
Abstract: In the collapsing phase of a molecular cloud, the molecular gas temperature is a key to understand the evolutionary process from a dense molecular cloud to stars. In order to know this, mapping observations in NH3 lines are required. Therefore, we made them based on the FUGIN (FOREST Unbiased Galactic plane Imaging survey with Nobeyama 45m telescope). The 6 maps were observed in NH3 (J, K) = (1, 1), (2, 2), (3, 3) and H2 O maser lines and obtained temperature maps; some show temperature gradient in a cloud. Additionally 72 cores were observed. These candidates were called as KAGONMA or KAG objects as abbreviation of KAgoshima Galactic Object survey with Nobeyama 45-M telescope in Ammonia lines. We show the results of two regions in W33 and discuss their astrophysical properties.